Safety and efficacy of insulin degludec/insulin aspart with bolus mealtime insulin aspart compared with standard basal–bolus treatment in people with Type 1 diabetes: 1–year results from a randomized clinical trial (BOOST® T1). Issue 2 (19th February 2016) - Hirsch, I. B.; Franek, E.; Mersebach, H.; Bardtrum, L.; Hermansen, K.
Abstract: Aims: To evaluate the long‐term safety and efficacy of a simplified basal–bolus regimen of once‐daily insulin degludec/insulin aspart (IDegAsp) with additional IAsp vs. a standard basal–bolus insulin regimen of insulin detemir (IDet) with IAsp in adults with Type 1 diabetes. Methods: This was an open‐label trial comprising a 26‐week core phase followed by a 26‐week extension phase. Participants were randomized to IDegAsp once daily at the main meal and IAsp at remaining meals (IDegAsp+IAsp), or IDet (once or twice daily) and IAsp at all meals (IDet+IAsp). Insulins were titrated to target plasma glucose of < 5 mmol/l (< 90 mg/dl) at pre‐breakfast (IDegAsp and IDet) and at pre‐meal (IAsp). Results: After 52 weeks, the overall confirmed hypoglycaemia rate was 31.8 episodes/patient‐years of exposure (PYE) with IDegAsp+Asp and 36.7 episodes/PYE with IDet+IAsp, and the rate of nocturnal confirmed hypoglycaemia was significantly lower with IDegAsp+Asp than with IDet+IAsp (3.1 vs. 5.4 episodes/PYE, respectively; P < 0.05). Adverse event rates were comparable between groups. Mean HbA1c decreased from baseline by 0.7% (IDegAsp+IAsp) and 0.6% (IDet+IAsp), achieving 60 or 61 mmol/mol (7.6% or 7.7%, respectively), at Week 52. The mean total daily insulin dose was lower with IDegAsp+IAsp than with IDet+IAsp (ratio: 0.87; 95% CI 0.79–0.95; P = 0.0026). Conclusions: Once‐daily treatment with IDegAsp and IAsp as bolus insulin for remaining meals was associated with significantly lower risk of nocturnal confirmed hypoglycaemia, improved glycaemic control and showed non‐inferiority compared with IDet+IAsp, the standard of care in Type 1 diabetes. What's new?: For people with Type 1 diabetes, modern‐day basal–bolus regimens requiring separate daily injections of basal and prandial insulin are the standard of care. To date, it has not been possible to combine basal and bolus insulin in a single injection (thereby reducing the injection number) without adversely affecting the glucose‐lowering properties of both components. Insulin degludec/insulin aspart (IDegAsp) is a combination of the basal insulin analogue, insulin degludec, and the rapid‐acting insulin analogue, insulin aspart. This Phase 3 trial presents the first long‐term safety and efficacy data comparing IDegAsp with mealtime bolus with a standard basal–bolus regimen in Type 1 diabetes.